THE RELATIONSHIP BETWEEN BIOMOTOR COMPONENTS AND SOCCER PLAYER'S SHOOTING SKILL: A META-ANALYSIS STUDY - Rivaldi, Tito; Hariadi, Imam; Hanief, Yulingga Nanda (JSES : Journal of Sport and Exercise Science, 2023)
Studies that examine the biomotor component and shooting skill have been widely carried out in the sports field. These kinds of studies explained that the biomotor component has a very positive effect on improving shooting skills in football. However, the results of each study tend to be different, so it is necessary to conduct an inclusive data analysis to provide comprehensive information about the importance of the biomotor component to improve the shooting skill of football players. This study examined the effect size test of the biomotor component on the shooting skill of football players. The research type used was a meta-analysis study. The data source in this study was Google Scholar. The search literatures were from various sources using keywords: “power” AND “precision” AND “reaction” AND “balance” AND “explosive power” AND “agility” AND “coordination” AND “soccer shooting” 230 articles were obtained which were then filtered based on inclusion and exclusion criteria and 11 articles were analyzed. The data analysis was carried out through the stages of identifying variables, identifying the value of r, transforming the value of r into a z distribution, which was the effect size of each study, calculating the variance, calculating the standard error of z, and calculating the summary effect. The summary effect calculation was using Jeffrey's Amazing Statistics Program (JASP) software. The results of the analysis using the random effects model showed that there was a significant positive correlation between the biomotor component and the shooting skill of soccer players (z = 6.018, p<0.001, 95%CI, (0.484; 0.951). The influence between the biomotor component and the shooting skill of soccer players was included in the high category (rRE=0,717). The results of the study can be concluded that the biomotor component has a positive loreational relationship with the shooting ability of soccer players.